Forecasting the Number of Participants of Social Security Agency’s (BPJS) Programs in Banyumas Regency for Contributory Beneficiaries (PBI) Category Using Fuzzy Time Series Cheng Method - Putri, Charista Aprilia; Mashuri, Mashuri (Jurnal Statistika SKEWNESS, 2025)
The Social Security Agency (BPJS) is an agency responsible for organizing the social security program for the community. It is found that the number of JKN PBI participants keeps on increasing each month as the services at BPJS improve. This research aims at predicting the number of JKN participants for PBI category for October 2023 based on the data on the number of JKN PBI participants in October 2022-September 2023 using the fuzzy time series Cheng method. Using the fuzzy time series Cheng method, it was predicted that in October 2023 the number of JKN PBI participants would be 1,040,000. In terms of its accuracy level, the forecasting using this method had an MSE value of 3.34 and MAPE value of 0.04%. Therefore, it could be concluded that the forecasting of JKN participants for PBI category was highly accurate.